First observation of vector boson pairs in a hadronic final state at the tevatron collider. - Aaltonen, T; Adelman, J; Akimoto, T; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2009)
We present the first observation in hadronic collisions of the electroweak production of vector boson pairs (VV, V = W, Z) where one boson decays to a dijet final state. The data correspond to 3.5 fb(-1) of integrated luminosity of pp[over ] collisions at sqrt[s] = 1.96 TeV collected by the CDF II detector at the Fermilab Tevatron. We observe 1516 + or - 239(stat) + or - 144(syst) diboson candidate events and measure a cross section sigma(pp[over ]-->VV + X) of 18.0 + or - 2.8(stat) + or - 2.4(syst) + or -1.1(lumi) pb, in agreement with the expectations of the standard model.